The Effect of Clinical Nursing Video-Based Learning on Nursing Students’ English Speaking Proficiency - wim banu Ukhrowi (Kayee: Jurnal Pendidikan dan Ilmu Sosial, 2026)
The ability to communicate effectively in English is a core competency for nursing professionals in the globalized healthcare landscape, yet many nursing students face challenges applying the language in real clinical settings. This study investigates the impact of authentic clinical video-based learning on the English speaking proficiency of 20 fourth-semester Bachelor of Nursing Science students, using a quantitative one-group pretest-posttest design with total sampling. Data were collected using a validated rubric assessing fluency, vocabulary accuracy, grammatical accuracy, and contextual appropriateness, then analyzed via Shapiro–Wilk test, paired samples t-test, and effect size calculation. Results showed a statistically significant improvement in all measured speaking domains (p < 0.001) with a very large effect size, where vocabulary accuracy saw the greatest gain. The findings confirm that integrating authentic clinical videos, role-play, and structured feedback effectively enhances students’ professional English communication skills and supports better preparation for clinical practice.